Cross-reactions between Legionella pneumophila (serogroup 1) and twenty-eight other bacterial species, including other members of the family Legionellaceae. - Collins, M T (1983)
Cross-reactions between Legionella pneumophila serogroup 1 and 28 other bacterial species were studied by various quantitative immunoelectrophoretic techniques. A sonicated L. pneumophila antigen and purified homologous rabbit antibody were used as a reference system. Few antigens (0 to 6) cross-reacted with non-Legionellaceae, but two were found in nearly all gram-negative bacteria tested (antigens no. 1 and 66). Antigen no. 66 of the L. pneumophila reference system was shown to be antigenically similar to the "common antigen" of Pseudomonas aeruginosa reported in many gram-negative bacteria. Greater than 85% of the antigens from L. pneumophila serogroup 1 cross-reacted with the other six serogroups of L. pneumophila. By contrast, Fluoribacter (Legionella) bozemanae, F. (L.) dumoffii, F. (L.) gormanii, and Tatlockia (Legionella) micdadei cross-reacted with only 45, 53, 39, and 43% of the reference system antigens, respectively. The antigenic relatedness of members of the Legionellaceae, expressed as a matching coefficient, is discussed in terms of its taxonomic significance. Serogroup-, genus-, and family-specific antigens are identified in the L. pneumophila reference system.